Intraoral scanners in children: evaluation of the patient perception, reliability and reproducibility, and chairside time—A systematic review - Serrano-Velasco, Diego; Martín-Vacas, Andrea; Paz-Cortés, Marta M.; Giovannini, Giovanni; Cintora-López, Patricia; Aragoneses, Juan Manuel (Frontiers in Pediatrics, 2023)
Purpose: The aim of this systematic review is to evaluate the perception of the patient, the chairside time, the reliability and/or reproducibility of intraoral scanners for full arch in pediatric patients. Methods: In accordance with the PRISMA 2020 statements, a data search was performed in four databases (Medline-Pubmed, Scopus, ProQuest and Web of Science). Studies were classified in three categories (patient perception, scanning or impression time and reliability and/or reproducibility). The resources, the data extraction and the quality assessment were carried out independently by two operators. The variables recorded were population characteristics, material and methods aspects and included country, study design and main conclusion. A quality assessment of the selected studies was performed with QUADAS-2 tool, and Kappa-Cohen Index was calculated to analyze examiner agreement. Results: The initial search obtained 681 publications, and finally four studies matching inclusion criteria were selected. The distribution of the studies in the categories was three for the analysis of the patient's perception and scanning or impression time; and two items to assess the reliability and/or reproducibility of intraoral scans. All included studies have a repeated measures – transversal design. The sample size ranged between 26-59 children with a mean age. The intraoral scanners evaluated were Lava C.O.S, Cerec Omnicam, TRIOS Classic, TRIOS 3-Cart and TRIOS Ortho. The quality assessment of the studies using QUADAS-2 tool revealed a low risk of bias while evaluating patient perception, but an unclear risk of bias in the analysis of accuracy or chairside time. In relation to the applicability concerns, the patient selection was of high risk of bias. All studies agreed that the patient perception and comfort is better with intraoral scanners in comparison with the conventional method. The accuracy or reliability of the digital procedure is not clear, being clinically acceptable. In relation with the chairside time, it depends on the intraoral scanner, with contradictory data in the different analyzed studies. Conclusion: Patient perception and comfort is significantly higher with intraoral scanners compared to the conventional impression method, but the evidence for reliability or reproducibility is not strong to date. However, the differences would be clinically acceptable.